The VITAAL Stepping Exergame Prototype for Older Adults With Major Neurocognitive Disorder: A Usability Study - Swinnen, Nathalie; de Bruin, Eling D.; Dumoulin, Chantal; Thalmann, Melanie; Guimarães, Vânia; De Jong, Jacqueline; Vandenbulcke, Mathieu; Vancampfort, Davy (Frontiers in Aging Neuroscience, 2021)
Purpose: This study investigates the usability of a stepping exergame in older adults with major neurocognitive disorder (MNCD) residing in a long-term care facility. Materials and methods: A mixed methods study was conducted. Participants played exergames for 30 minutes on one try-out session. During the exergames, the think aloud method was used, and field notes were taken by the observer. Following the exergames, participants completed the System Usability Scale (SUS) and a semi-structured in-depth interview about usability including their personal experiences. Audio files were transcribed and a thematic content analysis of the think aloud data, field notes and interviews were performed using NVivo 12. Results: Twenty-two participants with MNCD were included [mean age = 84.3±5.5 (70-95) years; 81.8% women; Short Physical Performance Battery score = 7.5 ± 3.2 (1-12), Montréal Cognitive Assessment score = 11.9±4.4 (2-19)]. System usability was rated “ok to good” with a mean SUS score of 57.8 (SD= 12.3) with scores ranging from 37.5 to 90.0. Five main themes emerged from the content analysis: (1) perceived user friendliness and acceptability of the exergames; (2) interactional experience; (3) motivational factors; (4) training modalities; and (5) risks. There were no adverse events nor dropouts. Conclusions: Participants evaluated the usability of the exergames positively. The results indicate that the stepping exergame is useable in older adults with MNCD.